The Free Trade Agreement Between the United States and Morocco. The Importance of a Gradual and Assymetric Agreement - (:unkn) unknown (My University, 2007)
The agreement recently signed between Morocco and the United States foresees several modalities in dismantling tariffs. Our simulations show that the various modalities of trade liberalization may have different impacts on the welfare, the rate of growth and the sectoral trade balance of these two countries. More precisely, our findings justify the interest of a gradual and asymmetrical agreement. In addition, the FTA between the US and Morocco will have a significant impact not only on trade between the two countries, but also on their trading relationships with other countries. The most important trade diversion will affect the EU and particularly France, which is Morocco's largest trading partner. It will also adversely affect the other North African countries. The FTA will thus offer the opportunity to Morocco to diversify its markets and its capabilities, which are currently focused on the EU, particularly on France and Spain.
Keywords: African Research